1975
DOI: 10.1038/bjc.1975.95
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine deaminase activity in leukaemia

Abstract: Summary.-Adenosine deaminase (EC 3.5.4.4., ADA) has been measured in the blast cells of 36 patients with acute lymphoblastic, acute myeloid, chronic myeloid and chronic myeloid blast crisis leukaemia. Particularly high levels were found in acute lymphoblastic and chronic myeloid blast crisis patients. The measurement of ADA may be useful diagnostically in the undifferentiated acute leukaemias and in detecting the early onset of blast crisis in chronic myeloid leukaemia. Possible reasons for the elevation of AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
2

Year Published

1976
1976
1987
1987

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(17 citation statements)
references
References 23 publications
1
14
0
2
Order By: Relevance
“…However, the marked increases of ADA activity in rapidly growing hepatomas (Fig. 3) anid in acute leukaemia cells (Smyth and Harrap, 1975;Meier et al, 1976) suggest that this enzyme may correlate with the process of malignant progression. A lack of correlation of ADA activity with cell proliferation per se seems to be indicated by the unchanged values in regenerating liver and neonatal liver.…”
Section: D)1scussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the marked increases of ADA activity in rapidly growing hepatomas (Fig. 3) anid in acute leukaemia cells (Smyth and Harrap, 1975;Meier et al, 1976) suggest that this enzyme may correlate with the process of malignant progression. A lack of correlation of ADA activity with cell proliferation per se seems to be indicated by the unchanged values in regenerating liver and neonatal liver.…”
Section: D)1scussionmentioning
confidence: 96%
“…Congenital deficiency of ADA is associated with the severe combined immunodeficiency syndrome (Giblett et al, 1972;Dissing and Knudsen, 1972;Parkman et al, 1975). In peripheral lymphoid cells from patients with chronic lymphocytic leukaemia, ADA levels were in the normal range (Scholar and Calabresi, 1973), but blast cells from patients with acute lymphoblastic leukaemia and acute myeloid leukaemia contained markedly higher ADA activity than normal peripheral leucocytes (Smyth and Harrap, 1975;Meier, Coleman and Hutton, 1976). Reid and Lewin (1957) found that ADA activity in a primary azo-dye-induced hepatoma was in the same range as in normal liver, and DeLamirande, Allard and Cantero (1958) showed that ADA specific activity in Novikoff hepatoma was twice that of normal rat liver.…”
mentioning
confidence: 99%
“…Recently, the activity of the enzyme adenosine deaminase (ADA) has been shown to have specific importance for the metab-olism of lymphocytes (2). Tissue distribution studies show that ADA is usually present in all the tissues of the body with the highest activity in lymphocytes (3) and thymocytes (4). Furthermore, congenital absence ofthis enzyme, which arises as an inborn error ofmetabolism, results in the syndrome of severe combined immunodeficiency (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…High values of ADA occur in the blast cells of patients with acute lymphocytic, acute myeloid, chronic mveloid and chronic myeloid blastic crisis leukaemia, (Smyth and Harrap, 1975). Because ADA was usually higher in lymphoblasts than myeloblasts, Smyth and Harrap postulated that measurement of ADA might be useful diagnostically in the undifferentiated acute leukaemias.…”
mentioning
confidence: 99%